The mediation effect of general self-efficacy in relation to procrastination and sense of coherence among adults with attention deficit hyperactivity disorder - Agnieszka Malinowska; Wojciech Rodzeń (PLoS ONE, 2026)
Procrastination, defined as a tendency to delay starting or finishing tasks despite awareness of negative consequences, is a common problem among adults diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). In the context of ADHD, procrastination not only exacerbates difficulties related to concentration and organization but also affects overall life functioning, interpersonal relationships, and mental health. Therefore, identifying protective factors that can mitigate the impact of procrastination on the lives of people with ADHD is crucial. The aim of this study was to underscore the importance of general self-efficacy as a potential intervention target for improving the psychological well-being in terms of the sense of coherence. The study involved 180 people aged 18–56 years. All the study participants had been diagnosed with ADHD, some of whom were undergoing therapy and pharmacological treatment. The participants filled out a self-report questionnaire consisting of demographic variable measurement and three psychometric tools. The results of the analyses indicated a negative relationship between procrastination and sense of coherence, as well as between procrastination and self-efficacy, and a positive relationship between self-efficacy and sense of coherence. The obtained results of the mediation analysis support the research hypothesis of a partial mediation effect that a self-efficacy weakens the relationship between procrastination and a sense of coherence. The study contributes to the understanding of ADHD in adults and highlights the critical role of psychological factors in managing its symptoms and improving quality of life.